DISPARITAS SIKAP PEMAAFAN DI KALANGAN MAHASISWA - Moh Khasan (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2019)
This study aims to determine the influence of: 1) the influence of the study program on forgiveness, 2) the influence of gender on forgiveness, 3) the background of the study program and gender interactively on forgiveness. The population of this study was the Syari'ah and Law Faculty students at UIN Walisongo Semarang. The sample in this study was taken by cluster random sampling. The number of selected samples is 81 people. Data collection is done by questionnaire technique. Data analysis using the mean difference test (t-test) and Two Path Variant Analysis. So in this study, forgiveness (Y) as dependent variable will be viewed from the background of the study program (X1) and gender (X2) as criteria. The results showed that: 1) Students of the Jinayah-Siyasah study program tended to have higher levels of forgiveness than students of Ahwal al-Syakhsiyyah and Muamalah study programs. The calculation of the F value at the 5 percent significance level shows F = 34,051 ≥ 3,119 = F (α = 0.05: 2, 75); 2) Male students tend to have a higher level of forgiveness than female students. The calculation of the F value at the 5 percent significance level shows F = 45,342 ≥ 3,968 = F (α = 0.05: 1, 75); 3) Interactively, the background of the study program and gender does not affect the level of student forgiveness. The result of the calculation of the F value at the 5 percent significance level shows F = -12.530 3.119 = F (α = 0.05: 1, 75)